If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying p = 2(261 + -1p) p = (261 * 2 + -1p * 2) p = (522 + -2p) Solving p = 522 + -2p Solving for variable 'p'. Move all terms containing p to the left, all other terms to the right. Add '2p' to each side of the equation. p + 2p = 522 + -2p + 2p Combine like terms: p + 2p = 3p 3p = 522 + -2p + 2p Combine like terms: -2p + 2p = 0 3p = 522 + 0 3p = 522 Divide each side by '3'. p = 174 Simplifying p = 174
| 5x-9=7x-18 | | 5(2x)-2x= | | G-c-14=11 | | (10x+3)+(7x+7)= | | -7(-4+x)=119 | | 8*6*6/6*8 | | s+15=6s | | 4x-1=-10+6x-6-5x | | 3/4K=1-1/3 | | 47=12+7m | | -x^2+6+9=0 | | 32=7n-3n | | 77÷(21÷3)-4^2=77/7-16=-5 | | 183-u=56 | | X+(-6)=x+21 | | x+6+4=2+5x | | 2(2x-8)=4(9-5x) | | 12x^2=18 | | 5-3*2+7= | | 253=43-w | | 19/4=-X-15/4X | | 3+4m=73 | | 2(2k-1)=4(k+-2) | | -v+165=69 | | 6b+3b+b= | | 2m+37=9m-5 | | (10+2x)(18+2x)=384 | | 2x+52+3x-35=180 | | 16-u=26/5 | | -8-8x=-193 | | -12=-3x-4+x | | 3x+(2x-1)=22 |